Positive effects of probiotics against alzheimer’s disease: A scoping review - Tjung, Vivienne; Azzahrah, Aisyah; Sari, Amelya Agusthina Ayu (Indonesian Nutrition Association, 2024)
Alzheimer's disease (AD) is a neurodegenerative disease related to elderly with subtle onset and progressive impairment of behavior and cognitive functions that is projected to increase without medical breakthroughs. Recent medication effectiveness is limited, only symptomatic treatment is available, none are curative, and variably palliative. Studies suggest an association between gut health and Alzheimer's progression through the “microbiome-gut-brain axis”. A scoping review was conducted to further explore the positive effects of probiotics on AD, highlighting potential of enhancing cognitive function, mitigating inflammation, and improving lipid profiles.